O ensino médio e a cultura digital : desafios e possibilidades de o uso do aparelho celular dentro da sala de aula - Ferreira, Damiana Andreia (Universidade Federal de São Carlos, 2022)
In contemporary society, the smartphone has become an indispensable tool both in leisure time and in work-related activities. In possession of the device, it is possible to film, photograph, send and receive messages on WhatsApp, access social networks, among others. Given the various services and applications, the cell phone can be seen as a useful tool in the teaching and learning process. However, in the scenario of the omnipresence of the screen, consumption exacerbated by audiovisual stimulus damages the subject's ability to concentrate.Based on the theoreticians of the Critical Theory of Society, the objective of the research is, in the digital culture scenario, to investigate the pedagogical potential of the cell phone, considering the high school level. The methodology adopted was the reflection and revitalization of the cultural industry concepts by Theodor W. Adorno and Max Horkheimer; and the concept of semiformation produced in the essay Theory of Semiformation, written by Theodor W. Adorno. Finally, selection and analysis of academic articles published in the last decade of the 21st century, which analyze the contribution of the mobile device in high school classes. That said, the first chapter of the research seeks to analyze and revitalize the concept of cultural industry. In the second chapter, analysis and revitalization of the concept of semi-formation. In the third chapter, based on the discussions held around the concept of cultural industry and semi formation, the articles selected for this research were examined from 3 categories: 1) the ways in which the contents are worked through the cell phone in teaching classes medium; 2) attention span and a3) relationship between teacher and student. It is concluded that, in times of digital culture, the cell phone through applications, educational softwares, games and the use of images and sounds, is capable to contribute to the teaching and learning process of young people and adolescents, however it is necessary to make a critical analysis of the damage caused to the subject's internal structure and the modification of the teacher-student relationship to think about a pedagogical proposal.
High school and digital culture: challenges and possibilities of using cell phones in the classroom
Keywords: Uso pedagógico; Ensino médio; Semiformação; Indústria cultural; Teoria crítica da sociedade; Cultura digital; Pedagogical use; High school; Semi-formation; Cultural industry; Critical theory of society; Digital culture; Smartphone; CIENCIAS HUMANAS::EDUCACAO